Penerapan Prinsip Akuntabilitas Lembaga Amil Zakat Dompet Amal Insani (Lazdai) Lampung - Zaqi Ilman Jiwandono; Bambang Utoyo; Noverman Duadji; Dedy Hermawan (Universitas Mataram, 2020)
An accountability is one of the important topics in scientific studies and public administration practice. This is because the public pays great attention to the implementation of policies, programs, projects and routine activities carried out by public sector institutions. However, in practice, we often find practices in public institutions that do not reflect accountability, especially in the zakat sector. This research uses descriptive research with a qualitative approach. Data collection techniques are observation, interviews and document review studies. The results of this study include the legal accountability of the application of rules or laws related to the collection of zakat that has not been applied, namely the preparation of the zakat collection report required by BAZNAS Bandar Lampung City twice a year and only once a year, the target of collecting zakat which refers to the Decree of the Minister of Religion of the Republic of Indonesia number 333 of 2015 that LAZ at the district / city level was able to collect as much as Rp. 3,000,000,000 (three billion rupiah) has not been successful, process accountability, program accountability, policy accountability. The accountability of the process of implementing the existing zakat collection procedure flow has been running effectively and efficiently. The process of internal obstacles consists of the lack of qualified human resources in terms of law and technology. The accountability of the zakat collection program is divided into two, counters and electronic. The policy accountability in the policy-making stages originates from the division meeting material which is then brought to the working meeting of the board of directors and executives for discussion.